ANALISIS KETERKAITAN PERUBAHAN PENGGUNAAN LAHAN SAWAH TERHADAP KESEJAHTERAAN MASYARAKAT DI KECAMATAN SUNGAI RAYA - Marpaung, Indrika Madeline; Tampubolon, Budiman; Christanto, Ludovicus Manditya Hari (Jurnal Pendidikan dan Pembelajaran Khatulistiwa (JPPK), 2023)
This study aims to investigate how the relationship between changes in paddy field land use to other forms of land use affects people's welfare. Welfare in this study is seen in 3 parameters, namely income, education and social change. The method used in this study is a mixed method, with a qualitative approach. The technique used to obtain data is mapping (remote sensing), as well as interviews. Mapping was carried out to answer research questions related to how the area of land change in the research area, which is ideally presented in a spatial approach. Interviews were conducted to examine more deeply research questions related to community welfare. From the results of the mapping it is known that the area in Sungai Raya Sub-District, which has the most conversions to paddy fields, is Sungai Raya Village. So the interviews were carried out purposively targeting the people of Sungai Raya Village, and with the snowball sampling technique. Information was obtained that farming communities who lost their paddy fields due to land conversion had to work other side jobs to supplement their income, and even had to leave work as farmers because their paddy fields had changed their function to settlements. While there is no significant relationship between the conversion of paddy fields to the fulfillment of access to education and social conditions.